Wpływ nauki na etykę życia gospodarczego na podstawie sporu o ceny drapieżne - Trojanowska, Hanna (Annales. Etyka w Życiu Gospodarczym, 2012)
Chicago School argues that the use of predatory strategy may not lead to a profit. Postchicago School, investigating this problem on the basis of game theory, argues just the opposite. This dispute on the basis of theoretical economics, has an impact on ethics in economic life. In a number of lawsuits companies rely on the views of the Chicago School to win, which raises the ethical concerns.